A Novel Solid Media-Free In-Planta Soybean (Glycine max. (L) Merr.) Transformation Approach - Muhammad Waqar Khan; Aaqib Shaheen; Xuebin Zhang; Yaser Hassan Dewir; Nóra Mendler-Drienyovszki (Life)
Soybean’s lengthy protocols for transgenic plant production are a bottleneck in the transgenic breeding of this crop. Explants cultured on a medium for an extended duration exhibit unanticipated modifications. Stress-induced somaclonal variations and in vitro contaminations also cause substantial losses of transgenic plants. This effect could potentially be mitigated by direct shoot regeneration without solid media or in-planta transformation. The current study focused primarily on developing a rapid and effective media-free in-planta transformation technique for three soybean genotypes (Wm82) and our newly developed two hybrids, designated as ZX-16 and ZX-3. The whole procedure for a transgenic plant takes the same time as a stable grown seedling. Multiple axillary shoots were regenerated on stable-grown soybean seedlings without the ectopic expression of developmental regulatory genes. An approximate amount of 200 µL medium with a growth regulator was employed for shoot organogenesis and growth. The maximal shoot regeneration percentages in the Wm82 and ZX-3 genotypes were 87.1% and 84.5%, respectively. The stable transformation ranged from 3% to 8.0%, with an average of 5.5%. This approach seems to be the opposite of the hairy root transformation method, which allowed transgenic shoots to be regenerated on normal roots. Further improvement regarding an increase in the transformation efficiency and of this technique for a broad range of soybean genotypes and other dicot species would be extremely beneficial in achieving increased stable transformation.